(untitled) (World Economics and Finance Bulletin, 2023)
The study aimed to introduce the concept of block chain technology, its features, objectives, and characteristics. It also aimed to define the accounting information system, its components, characteristics, and functions. The study examined the relationship and impact between the use of block chain technology and the accounting information system. To achieve its objectives, the study used a questionnaire as a tool to gather the necessary information from 47 Iraqi companies listed in the Iraqi stock market. Given the nature of the study and its objectives, the researcher used a descriptive analytical approach. The study found a statistically significant strong positive relationship between block chain technology and the accounting information system in the listed companies in the Iraqi stock market. It also found a statistically significant strong positive relationship between the dimensions of block chain technology usage and the accounting information system in the listed companies in the Iraqi stock market, with a correlation coefficient of 0.883. The study recommended designing an accounting system that is flexible enough to accommodate all the changes that occur with block chain technology transactions. It also recommended the availability of qualified individuals who possess the scientific and practical knowledge and are capable of performing accounting work in the context of block chain technology